Implementasi The Law of Repetition untuk Meningkatkan Kompetensi Mahasiswa dalam Membuat Laporan Keuangan Berbasis SAK ETAP - Juliana Juliana; Rosmida Rosmida (Politeknik Negeri Bengkalis, 2021)
This study purpose to determine the implementation of the law of repetition to improve student competencies in making financial reports based on SAK ETAP in Bengkalis State Polytechnic. The type of data used in this study is a combination of quantitative and qualitative data. The research data were obtained from Bengkalis State Polytechnic students of the Applied Public Accounting Accounting Study Program semester 6 (six). Data collection techniques in this research are interviews, documentation studies and tests. The results of this study were obtained based on the results of the tests of students of the Bachelor of Applied Accounting Program in Public Finance in the 6th semester (six) after being given training to carry out the test which had greatly improved value before being given training. The average value after being given training increased to 98.6 or if presented at 98%.